Continued Posttrial Benefits of Buprenorphine Extended Release: RECOVER Study Findings. Issue 2 (16th March 2023) - Boyett, Brent; Nadipelli, Vijay R.; Solem, Caitlyn T.; Chilcoat, Howard; Bickel, Warren K.; Ling, Walter
Abstract : Background: This analysis describes participants' opioid use disorder (OUD) outcomes for 18 months after discontinuing extended-release buprenorphine injection (BUP-XR, SUBLOCADE). Methods: The RECOVER (Remission From Chronic Opioid Use: Studying Environmental and Socioeconomic Factors on Recovery) study recruited participants from BUP-XR clinical trials (NCT02357901, NCT025100142, and NCT02896296) to assess whether there were sustained benefits after leaving the trial. Abstinence from opioids and from all illicit substances (excluding medical cannabis), health-related quality of life, depression, and employment were measured after BUP-XR discontinuation and change in outcomes assessed at 6, 12, and 18 months. Results were analyzed within the full cohort and by duration of BUP-XR treatment (0–2 months, 3–5 months, 6–11 months, 12 months, or 13–18 months) with and without inverse probability weights adjusting for differences in baseline characteristics. Results: Of 533 participants, 529 were assessed over the 18-month study period. Further posttrial pharmacotherapy was reported by 33% of participants. At RECOVER baseline, longer BUP-XR was associated with higher abstinence (0–2 months BUP-XR [n = 116]: 38.8%; 3–5 months BUP-XR [n = 61]: 41.0%; 6–11 months BUP-XR [n = 86]: 68.6%; 12 months BUP-XR [n = 135]: 71.9%; 18 months BUP-XR [n = 131]: 88.2%) and greater 12-Item Short Form Health Survey mental component scores. Over 60% of participants had stable or improved outcomes at 6, 12, and 18 months assessments. Overall 47% of participants self-reported sustained opioid abstinence for the full 18-month follow-up, with greater sustained abstinence associated with longer BUP-XR treatment duration. A sensitivity analysis, removing patients receiving medications for OUD, yielded similar results. Conclusions: Participants from BUP-XR clinical trials who continued into RECOVER maintained or improved on numerous outcomes over 18 months, demonstrating the long-term positive impact of OUD pharmacotherapy.